THE SIGNIFICANCE OF THE COURAGE AND HIGH ENDURANCE SHOWN BY OUR PEOPLE IN THE YEARS OF WORLD WAR II IN PATRIOTIC EDUCATION OF THE YOUNG PEOPLE - Valiyev Sarvar Abdisalimovich; Ergashev Hamidjon Komiljon o‘g‘li (Journals Park Publishing, 2023)
One of the most complex and responsible tasks of the initial period of the Soviet-German war was to put the economy on a military track.